INTEGRASI FIKIH, SOSIAL, DAN PELESTARIAN LINGKUNGAN (Studi tentang Kepemilikan Lubuk Larangan Koto Baru Solok) - Roki Ananda; Zainuddin Zainuddin (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
This study examines the integration of fikih, social and environmental preservation: a study of Lubuk Larangan ownership. The problem is the occurrence of saving the environment and social harmony after being given authority to the community to make Lubuk Larangan. From these problems, research questions arise: 1) what is the motivation of the community to establish lubukban, 2) what is the form of ownership of lubukban, 3) how is the social interaction of the community in the context of lubukban, 4). what is the form of environmental preservation in the context of lubuk ban. This research is a field research. Data obtained through observation and interviews. After the collected data is processed by means of data reduction, data presentation and drawing conclusions. Furthermore, the data is narrated descriptively. The results are discussed with the theories put forward. This study found that there is an integration of fiqh, social and environmental preservation. In the fiqh perspective, river ownership includes public ownership. Every community has rights and obligations in maintaining environmental sustainability which is manifested in the depths of the prohibition. Lubuk Prohibition can bind the bonds of brotherhood between communities for the better. The forms of this relationship are manifested in environmental preservation in the form of prevention of all pollution of the river environment, public awareness in improving river fish ecosystems, and regular provision of fish feed.